Food security among cocoa farming households of Ondo State, Nigeria (2009)
"In Nigeria, it has been documented that cocoa farmers devote most of their resources toward cocoa production at the detriment of food crop production because they derive more income from cocoa. There is, however, a dearth of information about the consequence of this practice on the food security status of cocoa farming households. In this study, the food security status of cocoa farming households of Ondo State, Nigeria was examined. Multistage sampling technique was used to select 200 respondent households from the study area in 2007. Information was collected from the respondents with the aid of structured questionnaire and the data obtained from the information were analyzed using Descriptive statistics, Food Security Index, Surplus/Shortfall Index and Probit model. The food security line was N2500.50 per month per adult equivalent. Based on this, 43% of the total sampled households were food secure while 57% were food insecure. Food secure households exceeded the calorie requirements by 12% while food insecure households fell short of calorie requirements by 9%. A unit increase in farming experience of household head (p<0.05), output of roots and tubers (p<0.05), output of cereals (p<0.05) and output of cocoa (p<0.01) increases the probability of household to be food secure by 0.0088, 0.00021, 0.000087 and 0.00049, respectively while a unit increase in household size (p<0.01) and age square of household head (p<0.1) decreases the probability of household to be food secure by 0.23 and 0.000074, respectively. A high percentage of households was food insecure, hence, cocoa farming households in the study area could be said to be food insecure "